Blood prolactin. Determination, normal and pathological - Garmendia Lorena, Fausto (2015)
It discloses the experience gained in the radioimmunoassay determination of prolactin (PRL) levels, both in terms of methodology and clinical. Normal, preliminary figures, obtained in 4 women and 4 normal males ranged from 3 to 26 ng / ml, average 17.4 ng / ml. In 12 patients with galactorrhea and / or amenorrhea high concentrations ranging between 33 and 195 ng / ml was found. One of 2 patients under sedative treatment presented hyperprolactinemia; likewise, April 2 acromnegálicos, 1 patient with "non-functioning" and impotence and 1 patient with primary hypothyroidism pituitary tumor. Conversely, 1 patient with panhypopituitarism traumatic fracture because of the skull base was not dosables PRL concentrations. Proof of I-dopa, held in 9 patients with galactorrhea and / or amenorrhea and in patients with pituitary tumor, revealed two types of responses: in 4 cases there is some variation was observed and the remaining 6 suppression was achieved concentration PRL which reached normal levels. The relative value of this test to differentiate organic functional disorders is discussed; It proposes instead a prognostic value type. an extensive review of the clinical manifestations of hyperprolactinemia is made and the importance of this methodology for the first time in our country, for the diagnosis of various clinical conditions that present with an exaggerated production of prolactin stands.